Leveraging Corporate-Startup Engagements: A Multiple Case Study Exploring Corporate Accelerators’ Post- Acceleration Activities - Dan,Cleo; Hackenberg,Tom; Wudarczyk,Dominik (2020)
This study focused on examining what post-acceleration startup management practices (‘activities’) corporate accelerators conduct and how these activities contribute to strategic value creation for the parent company. It was found that the post-acceleration phase is separated into three levels of post-acceleration activities and their strategic value contributions. Firstly, the resource level aims to deliver strategic value through knowledge and customer development to the parent company by providing resource-based post- acceleration support for the startups. Secondly, on the relationship-level, corporate accelerators build a close, informal and supportive partnership with the startups in order to promote innovation, new technology, and innovative talent. Thirdly, on the strategic-level, collaborations with the parent company and strategic investments through a corporate venture capital unit are facilitated in order to foster newstream and incremental innovation ability. Furthermore, within the strategic-level, it was found that corporate accelerators nurture a close relationship with corporate venture capital units to increase strategic value creation for the parent company.
Keywords: Corporate accelerators; corporate venture capital; corporate venturing; open innovation; corporate-startup engagement